Análise de desempenho de uma ferramenta de corte cerâmica reafiada na usinagem do ferro fundido nodular GGG-60 - Ribeiro, André Alonso (2016)
It was studied in this work the advantages and disadvantages of cutting tools reuse by regrinding. Through systematic monitoring of the inserts the performance of new tools and reground in machining nodular cast iron GGG-60 were compared. To achieve this goal it was performed the nodular cast iron milling with silicon nitride ceramic insert (Si3N4) New (IN) and reground (IR), where two cutting parameters were used, one recommended by the manufacturer of the tool (P2) and another optimized for pretesting (P1). Cutting fluid, an oil soluble mineral semisynthetic (FM) and a vegetable (FV) extracted from renewable sources were used to achieve a sustainable process. With Action 6.0 Software support it was held the experimental design (DOE) full factorial, with three independent variables on two levels. The following responses were evaluated: tool wear, surface quality of the workpiece (roughness) and power consumed. In the tests it was observed that the main wear mechanisms, both new tool or reground tool were abrasion and adhesion, leading flank wear. It was also noted that the reground tool increased surface roughness of the workpiece and the power consumption compared with the new tool. The best interaction statistically obtained for the process variables, in this type of machining, was found for the new tool (IN) with cutting parameters P1 and mineral cutting fluid (FM), but the attempt to define an economic and sustainable process cannot be ruled out.